A Framework to Support and Evaluate the Participation of Children with Autism in the Design of Technology - BOYLE, BRYAN GERARD (Trinity College Dublin. School of Computer Science & Statistics. Discipline of Computer Science, 2020)
As the availability of technology developed for children with autism has increased, an awareness of the benefits of designing technology with them has also improved. However, the intellectual, communication and social interaction deficits that characterize children with autism often see them overlooked as research or design participants. The objective of this thesis is to examine how children with autism can participate in the design of technology and to evaluate their participation. To this end, a two-stage ethnographic body of research composed of fourteen exploratory case-studies, conducted with sixteen children with autism, in a special education centre in the State of Qatar was undertaken. The first stage involved developing a framework to support the participation of children with autism in all the phases of the design process: early, intermediate and final. Data collected comprised observation, field notes, video and audio recordings, the design artefacts generated by the children and the final output for each design cycle. Data analysis consisted of, coding, categorisation, pattern analysis and cross-case synthesis. The second stage involved the articulation of a framework to evaluate the participation of children with autism in the design process. To assert the influence, impact and agency children with autism had on the design of technology, data collected in the first stage was examined through the lens of the evaluation framework. Findings illustrate the support framework facilitated the representation of the lived experience of children with autism in the designed output. Assisting children in the generation of creative content and evaluating design possibilities gave them a voice in guiding the direction of the design. The described framework ensured children with autism contributed to design decision making thus guiding the eventual design outcome. The evaluation of their participation reveals their impact, influence and agency in a design process is linked with harnessing their unique abilities and valuing their contributions.
APPROVED
Keywords: Children; Autism Spectrum Disorders; Participatory Design